Kloning gena cry dari Bacillus thuringiensis varietas kurstaki=Cloning of The cry Gene From Bacillus thuringiensis var. kurstaki - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Bacillus thuringiensis is an enthomopathogenic organism. The pathogenic effect is caused by crystalline protein known as 8- endotoxin, which encoded by cry gene. The aim of this research was to done the cry gene from B. thuringiensis var. kurstaki with the genomic library approach. The total DNA of B. thuringiensis var. kurstaki and pUC19 were digested with HindIII. The total DNA fragments were ligated to pUC19 which phosphatase treatment by calf intestinal phosphatase then transformed to Escherichia coli DH5a. Selection of transformants was done by a-complementation in media containing ampicillin, IPTG and X-gal. DNA containing the cry gene was identified by non radioactive hybridization method using a probe synthesized from the conserved region of cry genes. The result demonstrated that two recombinant plasmids, namely, pUD14 and pUD19 with the insert size of 3,4 kb and 2 kb, respectively, carrying the cry gene.